The Existence of The Garuda Jaya Pencak Silat and Bantengan Association in Lumbangrejo Village Prigen District Pasuruan District - Oktaviani, Nur Azizah; Sabri, Indar; Yanuartuti, Setyo; Nurhadi, Didik (PT. Hafasy Dwi Nawasena, 2024)
The Pencak Silat and Bantengan Garuda Jaya Association in Lumbangrejo Village, Prigen District, Pasuruan Regency, was established on October 1, 1982, specializing in Bantengan arts. This study aims to explore the history and current existence of this community using a descriptive qualitative approach, guided by James R. Brandon's theory of artistic life. Data were collected through observation, interviews, and documentation, and analyzed using triangulation techniques. The findings indicate that the association's existence is sustained by internal factors such as the artists, artistic quality, and management, as well as external factors like support from government institutions and socio-economic conditions. The study concludes that the association has adapted its performance structures to modern times, ensuring its continued relevance. Future efforts should focus on engaging the younger generation in learning and appreciating these traditional arts to preserve them for future generations.